Validity of Estimation of Pulmonary artery Pressure Using Continuous wave Doppler Echocardiography in Patient with Patent Ductus Arteriosus (PDA) - Ahmed, Chaudhury Meshkat; Arafat, Sohel Mahmud; Hasan, Muhammad Khaled; Khan, Abed Hussain; Sayami, Lima Asrin; Uddin Sultan, Md Ashraf; Hoque, Md Harisul; Mahmood, Manzoor (University Heart Journal, 2012)
Pulmonary artery pressure is one of the most important parameter for evaluating the status of pulmonary vascular bed for patients of PDA, which helps in formulating treatment strategy. This study was carried out in National Institute of Cardiovascular Diseases and Hospital (NICVD) and National Centre for Control of Rheumatic Fever and Heart Diseases, Dhaka, Bangladesh. Pulmonary artery pressure was recorded noninvasively using Doppler echocardiography and the it was correlated with those obtained from haemodynamic studies done at cardiac catheterization. Estimation of pulmonary artery pressure using Doppler derived measurement of pressure gradient across patent ductus arteriosus correlated well with that of simultaneous catheterization measured values. Doppler echocardiography is a cheap, simple, noninvasive bedside test for measuring pulmonary artery systolic and diastolic pressure in patient with PDA. DOI: http://dx.doi.org/10.3329/uhj.v7i1.10202 UHJ 2011; 7(1): 10-12